2023
DOI: 10.3390/ijms241813680
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Cognitive Decline, Focus on Microbiome: A Systematic Review and Meta-Analysis

Donatella Coradduzza,
Stefania Sedda,
Sara Cruciani
et al.

Abstract: Aging is a complex process influenced by genetics and the environment, leading to physiological decline and increased susceptibility to diseases. Cognitive decline is a prominent feature of aging, with implications for different neurodegenerative disorders. The gut microbiome has gained attention for its potential impact on health and disease, including cognitive function. This systematic review and meta-analysis aimed to investigate the relationship between the gut microbiome and cognitive function in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…During aging, the composition of the microbiome may change, influencing cognitive health [ 51 , 52 ]. As time progresses, microbiome diversity may decrease, potentially due to aging processes and cognitive decline [ 4 , 53 , 54 ]. Additionally, inflammatory processes may become more prevalent during aging [ 55 ], potentially harming brain structures and functions, indicating a bidirectional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…During aging, the composition of the microbiome may change, influencing cognitive health [ 51 , 52 ]. As time progresses, microbiome diversity may decrease, potentially due to aging processes and cognitive decline [ 4 , 53 , 54 ]. Additionally, inflammatory processes may become more prevalent during aging [ 55 ], potentially harming brain structures and functions, indicating a bidirectional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, there are considerable opportunities to investigate additional risk or protective factors that non-EHR studies have identified but were overlooked in the reviewed articles, including genetic markers (e.g., apolipoprotein E, presenilin 1 and 2, and amyloid precursor protein), 99 environmental toxins (e.g., lead, pesticides), 100 mild traumatic brain injury, 101 endocrine factors (such as hypothyroidism), sleep disturbance (like sleep apnea or chronic sleep deprivation), 8, 102 bilingualism, 103 vitamin and nutritional deficiencies, 104 and the microbiome (e.g., gut microbiome). 105 Fifth, while the existing literature primary focuses on dementia or AD, fewer studies address the early onset of AD and the initial stages of cognitive decline, such as mild cognitive impairment and subjective cognitive decline. Sixth, almost all the reviewed articles have used data from structured fields of the EHR.…”
Section: Discussionmentioning
confidence: 99%
“…This necessity has led researchers to shift their focus from the central nervous system (CNS) to other body systems, such as peripheral blood, in the study of neurodegenerative disorders [14]. Although neurocognitive conditions have traditionally been identified as pathologies affecting the neuronal sphere, with all studies and diagnoses focused on the CNS, the past few years have seen a shift from this neuro-centric vision [15,16]. Evidence revealed that the characteristic hallmarks of pathologies affecting neuronal cells can be identified in both neurons and peripheric cells [17][18][19][20][21] and that also other systems, outside the CNS, take part in the pathogenic process of neurocognitive disorders.…”
Section: Of 30mentioning
confidence: 99%